Intuitionistic Fuzzy Automaton for Approximate String Matching - K.M. Ravi; A. Choubey; K.K. Tripati (Fuzzy Information and Engineering, 2014)
This paper introduces an intuitionistic fuzzy automaton model for computing the similarity between pairs of strings. The model details the possible edit operations needed to transform any input (observed) string into a target (pattern) string by providing a membership and non-membership value between them. In the end, an algorithm is given for approximate string matching and the proposed model computes the similarity and dissimilarity between the pair of strings leading to better approximation.